Vocational Skills Guidance for the Independence of Visually Impaired Individuals at Wyata Guna Centre in Bandung - Mujiyono, Mujiyono; Sapari, Heri; Yurnalia, Anita; Saputra, Iqbal Khaerul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research is motivated by the lack of welfare for people with disabilities, so special guidance and attention are needed to improve their welfare. Sentra Wyata Guna Bandung is one of the institutions that provides services for people with disabilities, especially in the field of training and skills development. In this case, Sentra Wyata Guna Bandung guides people with disabilities in performing vocational skills in Massage and Shiatsu to achieve independence. This research uses Robert Havighurst's theory related to social welfare development, which includes emotional independence, economic independence, intellectual independence, and social independence. This research uses a qualitative descriptive method, describing vocational skills guidance for the independence of visually impaired individuals at Sentra Wyata Guna Bandung. The location of this research is in Bandung City, at Jl. Pajajaran No.50-52, Pasir Kaliki, Kec. Cicendo, Kota Bandung, Jawa Barat 40171. The results of this research show that the vocational skills guidance in massage and shiatsu provided by Sentra Wyata Guna Bandung can be considered optimal, but the time allocated is still insufficient. Additionally, the Vocational Skills Guidance in Massage and Shiatsu has enabled visually impaired individuals to achieve emotional independence, economic independence, intellectual independence, and social independence. However, inadequate facilities, delayed responses from visually impaired individuals in improving their vocational skills in massage and shiatsu, and insufficient time are factors that hinder the guidance process.